Clinical characteristics of the coronavirus disease 2019 (COVID-19) outbreak on a cruise ship - Yoshimura, Yukihiro; Sasaki, Hiroaki; Horiuchi, Hiroshi; Miyata, Nobuyuki; Tachikawa, Natsuo (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2020)
A large COVID-19 outbreak occurred on the cruise ship Diamond Princess in February 2020. Little information has been reported about the clinical characteristics of the patients. This single-center, retrospective, observational study was conducted in Yokohama, Japan. We included symptomatic patients who were infected on the ship and admitted to our hospital between 5 and 19 February 2020. All the cases were confirmed with SARS-CoV-2 infection by polymerase chain reaction (PCR). We confirmed 17 cases. The average age was 69 years; 10 patients were Asian and 7 were Caucasian. Eleven patients had one or more chronic diseases. The major symptoms were cough and fever. Chest computed tomography (CT) scans found bilateral ground-glass opacities predominantly in the peripheral area, which were similar to reports from cases in China. C-reactive protein (CRP) levels were higher in severe and critical cases than in mild to moderate cases. The moderate to severe cases reached symptomatic resolution; one of the three critical cases resulted in death due to multiple organ failure. SARS-CoV-2 was detected by PCR at an average of 7 days after symptomatic resolution. Cough and fever, increased blood CRP levels, and CT findings of bilateral ground-glass opacities predominantly in the peripheral lung were characteristic of the COVID-19 cases in this study. These findings were compatible with those of previous reports.